Expression Profiles of lncRNAs and circRNAs in Keloid - Wang, Jie (Plast Reconstr Surg Glob Open, 2019)
BACKGROUND: We hypothesized that crosstalk between noncoding RNAs, including microRNA (miRNA), lncRNA, and circRNA, might play a critical role in keloids development and physiology. To reveal the molecular mechanisms involved in the pathogenesis of keloids, we compared their gene expression profiles and differential expressions in keloid and normal skin tissues. METHODS: Expression profiles of mRNAs and lncRNAs and circRNAs in 2 pairs (identification set) of keloid and matched normal skin tissues were analyzed through sequencing. Real-time quantitative PCR was performed to validate the sequencing results using 5 pairs (validation set) of keloid and matched normal skin tissues. Presumed targets of differentially expressed lncRNAs and circRNAs were functionally annotated by bioinformatics approaches. RESULTS: The differential expression of mRNAs in keloid and normal skin by high-throughput sequencing was 2,528, of which 1,271 were downregulated, whereas 1,257 were upregulated. In the meantime, sequencing identified 2,227 differentially expressed lncRNAs, including 1,224 upregulated and 1,003 downregulated in keloid tissue compared with normal skin tissue. Additionally, 154 differentially expressed circRNAs were identified, including 81 upregulated and 73 downregulated in keloid tissue compared with normal skin tissue. Functional annotations of differentially expressed circRNA targets revealed their enrichment in several signaling pathways important for scar wound healing. CONCLUSIONS: Expression profiles of mRNAs, lncRNAs, and circRNAs were altered in keloid tissue, which may partly contribute to the etiology of keloids by affecting several signaling pathways relevant to scar wound healing. A better understanding of keloids pathogenesis may identify new therapeutic targets for keloids.